Probing the predictors of fraud using the Fraud Pentagon Theory - Pande Raja Sitanggang, Jhosua; Indrastuti, Dewi Kurnia (Media Bisnis, 2025)
This study aims to investigate how the elements of the fraud pentagon influence the prediction of financial statement fraud. The research identifies six independent variables: financial target, ineffective monitoring, auditor changes, director changes, the number of CEO photos, and personal financial need, while the dependent variable is financial statement fraud. The sample consists of companies from the energy, cyclical, and non-cyclical sectors listed on the Indonesia Stock Exchange, selected based on specific criteria, yielding 168 samples from 56 companies over the period from 2020 to 2022. A purposive sampling method was applied, and multiple regression analysis was conducted. The F-score model was utilized in this research to estimate the likelihood of financial statement fraud. The findings confirm that the independent variable of auditor changes has a positive effect on financial statement fraud, while the independent variable of the number of CEO photos exhibits a negative effects on financial statement fraud. Conversely, the independent variables of financial target, ineffective monitoring, director changes, and personal financial need do not appear to impact financial statement fraud.